The Influence of Digital Empathy, Online Identity Formation, Fear of Missing Out (FoMO), and Social Media Fatigue on the Mental Health of Adolescents in West Java - Wijayanti, Christina Nur; Ruth, Natasha (Westscience Press, 2025)
This study investigates the influence of digital empathy, online identity formation, fear of missing out (FoMO), and social media fatigue on the mental health of adolescents in West Java, Indonesia. Using a quantitative research design, data were collected from 175 adolescent respondents through a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3.0). The results reveal that digital empathy and online identity formation have a positive and significant effect on adolescents’ mental health, indicating that empathetic online behavior and authentic self-expression contribute to psychological well-being. Conversely, FoMO and social media fatigue demonstrate negative and significant effects, suggesting that excessive social comparison and emotional exhaustion reduce mental wellness. Moreover, social media fatigue mediates the relationship between FoMO and mental health, showing that digital overload acts as a psychological strain linking fear of exclusion to reduced well-being. The model explains 57% of the variance in mental health, indicating strong predictive power. These findings highlight the importance of cultivating digital empathy, promoting balanced online identity management, and implementing interventions to minimize FoMO and fatigue among youth. The study contributes to both theoretical understanding and practical strategies for enhancing adolescent digital well-being in the context of rapid social media engagement.